DESCRIPTION OF PARENTS-ADOLESCENT CONFLICT - Apriyeni, Emira; Machmud, Rizanda; Sarfika, Rika (Jurnal Endurance, 2019)
AbstractConflicts with parents has increased in adolescence. Conflict that tends to increase will have an impact on adolescent behavior problems. This study aims to describe parents-adolescent conflicts. The research desaign was descriptive with population is the students of Public Junior High School in Padang City with sample 388 sample using purposive sampling technique. This study used the Conflict Behavior Questionnaire questionnaire. The results obtained 44.1% of adolescents experiencing conflict with parents. It is recommended to nurses give health education on conflict management and assertive behavior to minimize sustained conflict.